The transcription factor Foxk1 is expressed in developing and adult mouse neuroretina - Sel, Saadettin; Münzenberg, Christoph; Naß, Norbert; Kalinski, Thomas; Datan, Maja; Auffarth, Gerd U.; Töteberg-Harms, Marc; Zenkel, Matthias; Kruse, Friedrich E.; Paulsen, Friedrich; Schicht, Martin (Gene expression patterns, 2013)
The forkhead transcription factor Foxk1 is an important regulator of myogenic progenitor cells. Since our previous data from mouse retina revealed that Foxk1 is upregulated in Ptf1a-deficient mice we investigated the spatial and temporal expression of Foxk1 during development of mouse retina. Expression of Foxk1 was analyzed on both mRNA and protein level. To identify Foxk1 transcripts, retina and cerebrum (positive control) of adult animals (postnatal day 90 (P90)) was subjected to reverse transcription polymerase chain reaction (RT-PCR) and sequencing of the amplified cDNA. The Foxk1 protein was analyzed in adult retina by Western blotting and in developing eyes at embryonic day (E) 13, 15, E17, P0, P4, P7, P10 and P90 by immunohistochemistry. Localization of Foxk1 expression was determined using cell-specific markers by double labelling. Foxk1 transcripts were detected in adult retina by RT-PCR and confirmed by sequencing. Western blot analysis confirmed the expression of Foxk1 protein in the adult retina. Immunohistochemical examination of developing eyes localized the protein to bipolar, amacrine and ganglion cells with an onset of Foxk1 expression from E15 onwards. The expression pattern during development suggests that Foxk1 may have an important role in retinal cells.